PENERAPAN MEDIA ANIMASI BERBASIS ANIMAKER MENGGUNAKAN CIRC (COOPERATIVE INTEGRATED READING AND COMPOSITION) TERHADAP HASIL BELAJAR SISWA - Huda, Muhammad Komarul; Saragih, Marlindoaman; Nuryah Ramadhani Saputri; Rajagukguk, Salome (Jurnal Metabio, 2024)
The purpose of this study was to determine whether the application of animation media based on animeker can improve student learning outcomes at SMA Perguruan Tamansiswa Pematangsiantar and to improve student learning outcomes on learning media using animated videos. This study uses a Classroom Action Research (CAR) model that refers to the research design including the stages: (1) planning, (2) action, (3) observation, (4) reflection. The sample in this study was the experimental class (XI MIPA 1) which consisted of 36 students. The results of the study were obtained from the data from using Animaker-Based Animation Using CIRC (Cooperative Intedred Reading And Composition) in cycles I and II, namely in cycle I 80% and in cycle II 85%.